2022
DOI: 10.1097/jnc.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Age and Mental Health Symptoms Among Chinese Persons With HIV: The Mediating and Moderating Role of Perceived Discrimination

Abstract: The association between age and mental health symptoms among persons with HIV (PWH) is inconsistent, and little is known about the mediators and moderators of this association. This study aimed to examine the association between age and mental health symptoms, as well as the mediators and moderators of perceived discrimination. Data were from 1,304 PWH who completed a cross-sectional survey in five areas of China. Multiple linear regressions showed that younger age was significantly associated with more severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…25,38,40,[63][64][65] Furthermore, recent studies have shown that in PLWH younger age is associated with lower mental quality of life 66 and with more severe mental health symptoms, in particular with a higher level of depression and anxiety. 67,68 We acknowledge that our study has some limitations. This is a cross-sectional study and uncontrolled biases can occur in routine clinical practice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25,38,40,[63][64][65] Furthermore, recent studies have shown that in PLWH younger age is associated with lower mental quality of life 66 and with more severe mental health symptoms, in particular with a higher level of depression and anxiety. 67,68 We acknowledge that our study has some limitations. This is a cross-sectional study and uncontrolled biases can occur in routine clinical practice.…”
Section: Discussionmentioning
confidence: 98%
“…25,38,40,6365 Furthermore, recent studies have shown that in PLWH younger age is associated with lower mental quality of life 66 and with more severe mental health symptoms, in particular with a higher level of depression and anxiety. 67,68…”
Section: Discussionmentioning
confidence: 99%